A new method of surface electromyography of direct eye muscles in children (Ukrainian Journal of Ophthalmology, 2026)
Purpose. The lack of objective methods to evaluate functions of the eye muscles, of special equipment and noninvasive methods of EMG among children led to develop an objective method for surface noninvasive electromyography of the direct eye muscles in children and to define their bioelectric activity. Material and methods. To conduct surface electromyography (SEMG) of the direct external muscles of the eyes computer electromyograph M-TEST-2 was applied. SEMG was conducted in 28 (56 eyes) healthy children at the age 13–17. Results. Considering the size of the direct external eye muscles and the distance of their attachment from the limb the two silver and platinum electrodes with 5 mm diameter and distance 6mm between them were modified. EMG characteristics in healthy children were defined. Conclusion. Suggested method of SEMG by M-TEST-2 and modified electrodes is informative, improved electrode (taking into account the middle width of muscle and place of it attachment on the eyeball) for 28 children at age 13–17 years. Received values of frequency and peak amplitudes of bioelectric activity of ocular muscles can be initial for comparative studies in concomitant strabismus.
Keywords: strabismus; external rectus muscles; electromyography